TUMBUHAN YANG DIKUNJUNGI LEBAH PEKERJA Apis (Hymenoptera: Apidae) DI SUMATERA BARAT - Jasmi, Jasmi (Sainstek : Jurnal Sains dan Teknologi, 2013)
Research about plant visited by Apis forager was conducted at altitude < 500 m and 600-1400 m of West Sumatra from December 2009-July 2010. The plant visited by forager was collected at radius 500 m from nests in fruits cropping, coffea and cinnamom plantation and forest edge. Honeybee from genus Apisvisit on plant consisted of four species, those are A. andreniformis, A. cerana, A. dorsata and A. koschevnikovi. Plant visited by forager Apis consisted of 61 species belong to 26 families. The number of 36 plant species found at lowland and highland, 20 species only at lowland and five species at highland. Most of plant species visited by Apis forager are Asteraceae and Leguminoceae. About 29 plant species visited by Apis were agriculture crop and 32 species of non agriculture. Apis andreniformis visited 29 plant species, A. cerana 56 species, A. dorsata 57 species and A. koschevnikovi one plant species. Cucumis sativus was visited by four bee species, Galiansoga farviflora was visited only by A. cerana. Five plant species (Rorippa indica, Cinnamomum burmanii, Nasturrium indicum, Rorippa indica and Eryngium foetidum) were visited by only A. dorsata. Other three plants species (Mangifera indica, Cytrus aurantifoliaand Oryza sativa) were visited by A. cerana and A. andreniformis, 31 plant species were visited by A. cerana and A. dorsata, 21 species were visited by A. andreniformis, A. cerana and A. dorsata.Keywords: lebah madu, Apis forager, food source plant, visit